The Anemia that Halted Treatment: A case of Complicated Hyperlipidemia - Mark M Mokhtar; Catherine E Lempke; Ruth Agwuna (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2018)
Familial hyperlipidemia is defi ned by abnormal levels of the following: low density lipoprotein cholesterol (LDL-C); high density lipoprotein cholesterol (HDL); triglycerides (TAG); or any combination of the three. Furthermore, while the disease is of a polygenic nature and at current time is poorly understood, it has been noted that the proteins apoB (needed for the LDL receptor and to aid in the removal of LDL from circulation) and apoE (which aids in the clearance of chylomicrons and very low density lipoprotein) present abnormalities in this illness [1]. With respect to apoB abnormalities, a Mendelian inheritance pattern has been observed in a number of cases despite the fact that familial hyperlipidemia is determined by interaction of multiple genes [2,3] and occurs in only 1-2% of the general population [4]. Anemia itself has numerous forms and causes, but the one that this paper will be focusing on will be iron defi ciency anemia. As this is a pediatric case, the thresholds will be for children 6 months to < 5 years of age, and are the same as those used by the World Health Organization: hemoglobin under 11g/dL and Ferritin <12 micrograms/L [5]. Iron defi ciency anemia is the most common form of anemia on the planet, ranging as high as 1 in 3 children less than 5 years of age [6].